2017
DOI: 10.1371/journal.pone.0189269
|View full text |Cite
|
Sign up to set email alerts
|

Coronary-to-pulmonary artery fistula in adults: Evaluation with thallium-201 myocardial perfusion SPECT

Abstract: ObjectivesWith the increasing use of multi-detector CT, the number of detected cases with coronary-to-pulmonary artery fistula (CPAF) has increased. Several previous studies reported severe cases of angina, but no appropriate tests to evaluate myocardial perfusion for patients with CPAF have been established. We evaluated the hemodynamic characteristics of CPAF using thallium-201 (Tl-201) single photon emission computed tomography (SPECT).Materials and methodsTl-201 SPECT was performed in 17 patients with CPAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…According to the 2008 ACC/AHA guidelines, CAFs that should be evaluated for closure are large fistulas regardless of symptomology, and small to moderate fistulas that are associated with myocardial ischemia, arrhythmia, endarteritis, unexplained ventricular diastolic or systolic dysfunction, and ventricular dilation [17]. If a CAF is incidentally discovered on imaging and considered to be the etiology of angina, myocardial ischemia can be evaluated with exercise stress testing or myocardial perfusion scanning [3,27,30]. CAF size characterization is defined with angiography and in reference to the distal vessel lumen, with a large CAF being greater than 2x the diameter of the distal vessel, and small to moderate being less than 1–2x the distal vessel diameter [20].…”
Section: Discussionmentioning
confidence: 99%
“…According to the 2008 ACC/AHA guidelines, CAFs that should be evaluated for closure are large fistulas regardless of symptomology, and small to moderate fistulas that are associated with myocardial ischemia, arrhythmia, endarteritis, unexplained ventricular diastolic or systolic dysfunction, and ventricular dilation [17]. If a CAF is incidentally discovered on imaging and considered to be the etiology of angina, myocardial ischemia can be evaluated with exercise stress testing or myocardial perfusion scanning [3,27,30]. CAF size characterization is defined with angiography and in reference to the distal vessel lumen, with a large CAF being greater than 2x the diameter of the distal vessel, and small to moderate being less than 1–2x the distal vessel diameter [20].…”
Section: Discussionmentioning
confidence: 99%
“…A report by Gupta et al[ 46 ] in 1991, followed by Glynn et al[ 47 ] in 1994, reported the first case studies documenting the use of thallium-201 perfusion imaging for physiological assessment of CAF (LAD-PA) and as the cause of an exercise-induced reversible thallium-201 perfusion defect in an adult patient[ 46 , 47 ]. The pharmacological stress MPI SPECT technique may indicate segmental perfusion defects in patients with congenital CPF in the absence of CAD[ 11 ]. In a patient series evaluated by Lee et al[ 11 ], 35% of patients with congenital CPF without CAD developed perfusion defects, but the findings were only clinically relevant in 12%.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological stress MPI SPECT technique may indicate segmental perfusion defects in patients with congenital CPF in the absence of CAD[ 11 ]. In a patient series evaluated by Lee et al[ 11 ], 35% of patients with congenital CPF without CAD developed perfusion defects, but the findings were only clinically relevant in 12%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations